In dialogue with, within, and beyond depletion - Montgomery, David R.; Denizen, Seth; Thomas, Laura (Journal of Delta Urbanism, 2025)
This dialogue brings together geomorphologist David R. Montgomery and landscape architect Seth Denizen to explore ideas of depletion in soil and deltaic landscapes. Moderated by Laura Thomas, the conversation considers depletion both as a physical condition at different scales and as a situated judgment. Across deltas, megacities, and agricultural hinterlands, the participants discuss soil as both an ecological foundation and a site where social relations are produced. Both speakers highlight how soils are shaped by complex social and material processes that actively contribute to their formation. They raise caution that reducing all questions of soil health to a single number is reductive, and that the way scientific problems around soil health are framed can obscure the bigger picture. Moments of synthesis, they suggest, require interdisciplinary collaboration to connect political ideas to their ecological foundations. The dialogue also emphasizes that urban soils are not isolated but connected to rural hinterlands. Linking urban planning, soil science, and health, they argue, could help reduce conflicts over scarce resources and support urban adaptation. In closing, the conversation turns to regenerative futures. If depletion signals systems pushed beyond their limits, what possibilities emerge when it is treated as a starting point? The speakers reflect that rethinking our relationship with soils involves paying close attention to the processes that brought us here: processes that are deeply political and can only be addressed through conversation and collective action.